Early trends in serum phosphate and creatinine levels are associated with mortality following major hepatectomy. Issue 12 (19th September 2015) - Herbert, Garth S.; Prussing, Kara B.; Simpson, Amber L.; D'Angelica, Michael I.; Allen, Peter J.; DeMatteo, Ronald P.; Jarnagin, William R.; Kingham, T. Peter
Abstract: Background: Mortality after major hepatectomy remains high and is frequently related to post‐hepatectomy liver failure (PHLF). Other than pre‐existing liver disease and a small future liver remnant, few patient factors or early postoperative indicators identify patients at elevated risk for PHLF and mortality. Methods: Data on demographics, comorbidities, operative procedures and postoperative laboratory trends were reviewed for patients submitted to major hepatectomy (at least three Couinaud segments) for malignancy during 1998–2013. These factors were compared among patients who died within 90 days, survivors who met the 50–50 criteria and all remaining survivors. Results: A total of 1528 patients underwent major hepatectomy during the study period. Of these, 947 had metastatic colorectal cancer and underwent resection of a median of four segments. Overall, 49 patients (3.2%) died within 90 days of surgery and 48 patients (3.1%) met the 50–50 criteria for PHLF; 30 of these patients survived 90 days. Operative blood loss was higher in patients who died within 90 days compared with survivors (1.0 l versus 0.5 l; P  < 0.001). Despite equivalent perioperative resuscitation and urine output, non‐survivors had higher creatinine and phosphate levels than survivors on postoperative day (PoD) 1 (1.1 mg/dl versus 0.9 mg/dl and 4.6 mg/dl versus 3.7 mg/dl, respectively; P  < 0.001). Conclusions: Early trends in creatinine and phosphate (between the day of surgery and PoD 1) identify patients at risk for PHLF and mortality.